1994
DOI: 10.1007/bf02054413
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, endoscopic-blinded trial comparing precolonoscopy bowel cleansing methods

Abstract: The smaller volume oral sodium phosphate was not associated with any clinically significant problem, caused no increase in the incidence of side effects, was preferred by patients, and was more effective in colonic cleansing. However, the hyperphosphatemia seen may limit its use in patients with impaired renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
156
2
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(169 citation statements)
references
References 28 publications
8
156
2
3
Order By: Relevance
“…A single patient reached a serum phosphorus level of 11.6 mg/dl (4). A larger study examined electrolyte changes in 143 patients who received OSPS and found a mean increase in serum phosphorus of 3 mg/dl and a mean decline in serum calcium of 0.3 mg/dl (5). A more recent study found that older patients achieve greater levels of hyperphosphatemia after use of OSPS (6).…”
Section: Discussionmentioning
confidence: 99%
“…A single patient reached a serum phosphorus level of 11.6 mg/dl (4). A larger study examined electrolyte changes in 143 patients who received OSPS and found a mean increase in serum phosphorus of 3 mg/dl and a mean decline in serum calcium of 0.3 mg/dl (5). A more recent study found that older patients achieve greater levels of hyperphosphatemia after use of OSPS (6).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, none of the preparations meets all of the requirements [2][3][4] . Several studies have evaluated the efficacy and side effects of regimens for bowel preparation [3][4][5][6][7][8][9][10][11][12][13][14] . In 2006, three medical organizations (the American Society for Gastrointestinal Endoscopy, the American Society of Colon and Rectal Surgeons, and the Society of American Gastrointestinal and Endoscopic Surgeons) suggested that polyethyleneglycol (PEG) should be a gold standard for colonoscopic bowel preparation (Grade IA), and aqueous sodium phosphate (NaP) was an alternative regimen to PEG solution (Grade IA) [2] .…”
Section: Introductionmentioning
confidence: 99%
“…
Bowel preparations containing oral so− dium phosphate have gained increased favor among gastroenterology endosco− pists in preference to the traditional poly− ethylene glycol, likely due to greater pa− tient tolerability and improved cleansing and compliance [1]. Despite the availabil− ity of reports in the literature concerning life−threatening metabolic and cardiac abnormalities associated with the use of oral sodium phosphate in patients with renal insufficiency, less than half of re− spondents in a recent survey among gas− trointestinal endoscopists reported its ex− clusion in this patient population [2].
…”
mentioning
confidence: 99%